The information transmission and risk contagion effect between green bond market and government bond market in China - Zhou, Xinmiao; Lu, Hongyuan; Ye, Shengchao (Frontiers in Environmental Science, 2023)
The problem of correlation between the Chinese green bond market and the government bond market may affect the smooth operation of the national economy. In this paper, a total of 3,181 sets of data representing the China’s green bond market and the government bond market for the period 2010–2022 are selected, and the VECM-DCC-VARMA-AGARCH model is used to analyse the spillover effects between the two in terms of information transmission and risk contagion. The results indicate that (1) The dynamic correlation between the China’s green bond market and the government bond market is significant, with obvious information transmission and risk contagion effects. (2) Compared to the government bond market, the green bond market is more sensitive to new information and the intensity of the reflection is stronger. (3) There is a long-term equilibrium relationship between the China’s green bond market and the government bond market, and the government bond market will adjust in the direction of green bonds through an error correction mechanism when deviations occur. (4) There is a significant two-way risk contagion effect between the green bond market and the government bond market, but the intensity of the effect is asymmetric. (5) The dynamic correlation between the green bond market and the government bond market has been deepening. Based on the above findings, we have put forward some rationalisation proposals.